Inhibition of methanol extract snail gonggong (Strombus urturella) to pathogenic bacteria Vibrio alginolyticus - Frans Selfanay; Syahran Wael; Theopilus Wilhelmus Watuguly (Program Studi Pendidikan Biologi, Pascasarjana, Universitas Pattimura, 2022)
The purpose of this study was to determine the methanol extract of snail gonggong (Strombus turturella) and the inhibition of methanol extract of gonggong snail meat (Strombus turturella) against the pathogenic bacterium Vibrio alginolyticus. The study used a completely randomized design. The treatment was giving the extract of snail gonggong meat with concentration of 100%, 50%, 25%, positive control using amoxcillin and negative control using distilled water with three replications. The identification of bioactive compounds included alkaloids, saponins, flavonoids, steroids and triterpenoids. The antibacterial activity of the methanol extract of snail gonggong meat (Strombus turturella) was tested by the diffusion method at concentrations of 100%, 50% and 25%. The data collected is then analyzed descriptively qualitatively. The results showed that the antibacterial activity of the 100% concentration of the methanol extract of the gonggong snail meat had moderate inhibition against Vibrio alginolyticus (diameter 7,833 mm). while the concentrations of 50% and 25% did not have an inhibition zone. The identified bioactive compounds included alkaloids, saponins, flavonoids and steroids, while the terpenoid and phenolic compounds were not identified. Thus, the methanol extract of gonggong snail meat has antibacterial potential that can be used to overcome the attack of pathogenic bacteria.